2016
DOI: 10.2147/ijn.s99945
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of B-cell lymphoma/leukemia-2 by overexpressed microRNA 34a enhanced titanium dioxide nanoparticle-induced autophagy in BEAS-2B cells

Abstract: Titanium dioxide (TiO 2 ) nanoparticles (TNPs) are manufactured worldwide for a wide range of applications and the toxic effect of TNPs on biological systems is gaining attention. Autophagy is recognized as an emerging toxicity mechanism triggered by nanomaterials. MicroRNA 34a (miR34a) acts as a tumor suppressor gene by targeting many oncogenes, but how it affects autophagy induced by TNPs is not completely understood. Here, we observed the activation of TNP-induced autophagy through mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…[88] Previous studies have suggested that TiO 2 NPs have a regulative effect on autophagy. [41,42] It has been demonstrated that TiO 2 NPs activated protective autophagy in a dose-dependent manner after acting on primary human keratinforming cells. [89] Similarly, TiO 2 NP-induced protective autophagy in podocytes was attained by activating the AMPK/mTOR pathway.…”
Section: Ionps Have Been Described To Activate Autophagy In Gbm Cells...mentioning
confidence: 99%
“…[88] Previous studies have suggested that TiO 2 NPs have a regulative effect on autophagy. [41,42] It has been demonstrated that TiO 2 NPs activated protective autophagy in a dose-dependent manner after acting on primary human keratinforming cells. [89] Similarly, TiO 2 NP-induced protective autophagy in podocytes was attained by activating the AMPK/mTOR pathway.…”
Section: Ionps Have Been Described To Activate Autophagy In Gbm Cells...mentioning
confidence: 99%